Testing for wildfire feedbacks in forests of the US Northern Rockies - Harvey, Brian J. (Proceedings of the Wisconsin Space Conference, 2015)
Understanding the complex responses of forested landscapes to changing fire regimes is critical for predicting land-cover patterns under a warming climate. Using decades of existing NASA satellite imagery and extensive field-calibration data on burn severity I tested whether successive forest fires in the Northern Rocky Mountains interact through feedbacks, and identified factors that are more likely to lead to two successive high-severity (stand- replacing) fires. Feedbacks among wildfires depended on forest type and interval between the first and second fire. Feedbacks in wildfire severity shifted from negative to positive with increasing elevation and with interval between two fires. Areas characterized by two successive stand-replacing fires were in subalpine forests at higher elevations, shallower slopes, and northeasterly aspects where the interval between fires was longer. Further analyses are underway, and results will identify when and where fire-catalyzed shifts in vegetation are occurring or are likely to occur with continued climate change and altered fire regimes.